Mapping the Simultaneously Accessible and ssDNA-Containing Genome With KAS-ATAC Sequencing - Georgi Marinov; William Greenleaf (Bio-Protocol)
The KAS-ATAC assay provides a method to capture genomic DNA fragments that are simultaneously physically accessible and contain single-stranded DNA (ssDNA) bubbles. These are characteristic features of two of the key processes involved in regulating and expressing genes—on one hand, the activity of cis-regulatory elements (cREs), which are typically devoid of nucleosomes when active and occupied by transcription factors, and on the other, the association of RNA polymerases with DNA, which results in the presence of ssDNA structures. Here, we present a detailed protocol for carrying out KAS-ATAC as well as basic processing of KAS-ATAC datasets and discuss the key considerations for its successful application.